2020
DOI: 10.3390/brainsci10060346
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin and Integrin Mediated Modulation of Post-Synapses in HIV Envelope Glycoprotein Exposed Hippocampal Neurons

Abstract: The advent of Human Immunodeficiency Virus (HIV) antiretrovirals have reduced the severity of HIV related neurological comorbidities but they nevertheless remain prevalent. Synaptic degeneration due to the action of several viral factors released from infected brain myeloid and glia cells and inflammatory cytokines has been attributed to the manifestation of a range of cognitive and behavioral deficits. The contributions of specific pro-inflammatory factors and their interplay with viral factors in the setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 64 publications
(104 reference statements)
0
16
0
Order By: Relevance
“…Interestingly, suppression of OPN/SPP1 in uninfected control mice did not change basal neuroinflammation 115 . These results demonstrate that OPN/SPP1, by mechanisms that remain to be defined, (1) senses pathologic changes in brain homeostatic states and (2) regulates the neuroinflammatory response 68 . Interestingly, in HIV‐infected mice, a specific region of the brain known as the striatum, a region necessary for cognitive function, decision‐making, and reward, showed intense labeling for TSPO 115 .…”
Section: Crosstalk With a Microglial‐nigrostriatal Neuroinflammatory ...mentioning
confidence: 78%
See 3 more Smart Citations
“…Interestingly, suppression of OPN/SPP1 in uninfected control mice did not change basal neuroinflammation 115 . These results demonstrate that OPN/SPP1, by mechanisms that remain to be defined, (1) senses pathologic changes in brain homeostatic states and (2) regulates the neuroinflammatory response 68 . Interestingly, in HIV‐infected mice, a specific region of the brain known as the striatum, a region necessary for cognitive function, decision‐making, and reward, showed intense labeling for TSPO 115 .…”
Section: Crosstalk With a Microglial‐nigrostriatal Neuroinflammatory ...mentioning
confidence: 78%
“…The disruption of homeostatic plasticity likely underlies several neurological and neuropsychiatric disorders, given the direct evidence for alterations in integrin expression and positive associations with specific allelic variants 36 . We found that changes in PNN density were regulated in a differential fashion by signaling through β1‐ or β3‐integrins in the presence of HIV Env and OPN/SPP1 68 . Based on what is currently known about the contributions of PNN to signal propagation, we suggest that OPN/SPP1, in its role as an extracellular matrix protein, facilitates proper signal transmission.…”
Section: A Sensor Of Cns Injury and Inducer Of Neuroprotective Signalingmentioning
confidence: 85%
See 2 more Smart Citations
“…In postmortem examination, the levels were also elevated in brain tissue of patients with HAND [129]. Similarly, in postmortem brain tissue, perineuronal nets (PNNs)-degrading enzyme was increased in HAND and OPN was abundant in the HIV-infected brain [130,131].…”
Section: Acquired Immune Deficiency Sndrome (Aids)mentioning
confidence: 92%